2015
DOI: 10.1371/journal.pone.0125466
|View full text |Cite
|
Sign up to set email alerts
|

Using Community-Based Participatory Research Principles to Develop More Understandable Recruitment and Informed Consent Documents in Genomic Research

Abstract: BackgroundHeart Healthy Lenoir is a transdisciplinary project aimed at creating long-term, sustainable approaches to reduce cardiovascular disease risk disparities in Lenoir County, North Carolina using a design spanning genomic analysis and clinical intervention. We hypothesized that residents of Lenoir County would be unfamiliar and mistrustful of genomic research, and therefore reluctant to participate; additionally, these feelings would be higher in African-Americans.MethodologyTo test our hypothesis, we c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
47
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(48 citation statements)
references
References 26 publications
1
47
0
Order By: Relevance
“…Previous community-based genetic studies in the USA have been broadly population-based or primarily focused on racial and ethnic minorities, including African-American communities and Native American tribes, but there is little research that has been done looking at isolated rural populations of European descent (Foster et al 1999;Terry et al 2012;Rotimi et al 2007;Skinner et al 2015). Our group has hypothesized that the nature of the founding of many rural communities in the USA may have facilitated the development of genetic founder effects which may contribute to underlying disease risk variability (Jenkins et al 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous community-based genetic studies in the USA have been broadly population-based or primarily focused on racial and ethnic minorities, including African-American communities and Native American tribes, but there is little research that has been done looking at isolated rural populations of European descent (Foster et al 1999;Terry et al 2012;Rotimi et al 2007;Skinner et al 2015). Our group has hypothesized that the nature of the founding of many rural communities in the USA may have facilitated the development of genetic founder effects which may contribute to underlying disease risk variability (Jenkins et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Focus groups allow for participants to provide open-ended feedback and an additional avenue for community engagement and establishing a foundation of trust that can facilitate genetic research, as the community is often engaged in this qualitative research not only as participants but as Brecruiters^of participants. Including the community in the recruitment process has been effective for both community-based focus groups and genetic research (Cristancho et al 2008;Skinner et al 2015). Focus group findings have provided researchers with better information how to better consider community concerns, recruit research participants, and disseminate research findings in genetic research (Rotimi et al 2007;Terry et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, these ethical concerns have led researchers to consider a variety of processes to obtain community input into genomic research and increase community interest in potential results (George et al 2014;Green et al 2011;Millon Underwood et al 2013;Skinner et al 2015;Yu J-H and Burke W 2012). These processes have included conducting community interviews, focus groups, and rapid ethnographic assessments (Skinner et al 2015;Tindana et al 2012) to identify perceptions and barriers to participate in community-based genetic studies; and working with communities through community advisory boards (Quinn 2004), community fora (Mascalzoni et al 2008) and community consultations (Dickert and Sugarman 2005) to increase engagement of community members in conducting genomic studies.…”
Section: Introductionmentioning
confidence: 99%
“…These processes have included conducting community interviews, focus groups, and rapid ethnographic assessments (Skinner et al 2015;Tindana et al 2012) to identify perceptions and barriers to participate in community-based genetic studies; and working with communities through community advisory boards (Quinn 2004), community fora (Mascalzoni et al 2008) and community consultations (Dickert and Sugarman 2005) to increase engagement of community members in conducting genomic studies. Several genomic studies have reported successful outcomes using various community engagement processes Marsh et al 2013;Marsh et al 2010;Skinner et al 2015;Tindana et al 2012;Vreeman et al 2012), and particularly in designing an informed consent process with appropriate vocabularies that address more complex ethical issues, such as whether or not genetic data should be given to participants (Lemke et al 2012;Skinner et al 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation